Ultrasound measurement of optic nerve sheath diameter for intracranial pressure monitoring - Jiukun Jiang; Xiujing Xie (Interdisciplinary Neurosurgery, 2025)
Changes in optic nerve sheath diameter reflect intracranial pressure (ICP) variations and can serve as indicators for noninvasive ICP measurements. This review explores the literature on the anatomical foundations of changes in the optic nerve sheath diameter in response to ICP fluctuations, diagnostic threshold for elevated ICP and conversion formula, covers advances in research on monitoring the optic nerve sheath diameter in primary neurological conditions, primary non-neurological conditions, and the perioperative period, and discusses the procedure, benefits, and future research directions for ultrasound examination of the optic nerve sheath diameter, aiming to promote clinical study and application.